Role of human corneal endothelial cells in T-cell-mediated alloimmune attack in vitro - Lahdou, Imad; Engler, Christoph; Mehrle, Stefan; Daniel, Volker; Sadeghi, Mahmoud; Opelz, Gerhard; Terness, Peter (Investigative ophthalmology & visual science, 2014)
Human corneal endothelial cells (HCEC) are a potential target of immune attack after corneal transplantation. The aim of this in vitro study was to investigate the role of HCEC during the alloimmune response of T-cells by examining cytokine profiles, function of the immunosuppressive enzyme indoleamine 2,3-dioxigenase (IDO), major histocompatibility complex (MHC-I/-II), T-cell proliferation, and the induction of cell death. Real-time PCR and RP-HPLC were used to determine IDO expression and activity. Multiplex assay was performed for quantification of cytokine levels. T-cell proliferation was assessed by thymidine incorporation, and HCEC cell death was measured by flow cytometry. Human corneal endothelial cells induce strong proliferation of allogeneic T-cells and an increase of proinflammatory cytokines such as interleukin-1α (IL-1α), IL-1β, IL-6, interferon-gamma (IFN-γ), and tumor necrosis factor-alpha (TNF-α). Tumor necrosis factor-alpha (and to a lesser extent IFN-γ) induces apoptosis. Moreover, IFN-γ strongly upregulates MHC-II molecules and IDO activity in HCEC as reflected by high kynurenine (Kyn) concentrations. Interestingly, the T-cell response was not affected by increased IDO activity, since blocking of IDO did not affect the proliferation rate. Indoleamine 2,3-dioxigenase-induced Kyn levels did not exceed concentrations of 175 ± 20 μM. Concentrations of ≥400 μM Kyn were required to suppress T-cell proliferation. Our data show that T-cell attack on HCEC leads to increased concentrations of proinflammatory cytokines. Inflammatory cytokines induce apoptosis and upregulate MHC-II molecules and IDO in HCEC. Although increased IDO activity does not influence the T-cell response, it constitutes an inflammatory marker of the alloimmune response toward HCEC.